Parenting a Child with a Developmental Disability: An Autoethnographic Approach to Sensemaking - (:unkn) unknown (My University, 2017)
Each year, approximately one in six children are diagnosed with a developmental disability (DD) in the United States according to the CDC (Developmental Disabilities, 2015). In 2015, my daughter fell severely ill with encephalitis and became part of this statistic. Parenting a child with a DD can be an extremely isolating (Naseef, 2001) and even scary experience. However, storytelling helps individuals process experiences, connect with others, and shed light on their perspectives. Parents can become informed through these shared experiences, build supportive communities, develop resilience, and transform their perspectives. Using the qualitative research method of autoethnography, I approached my work through narrative to systematically analyze my experience as a mother navigating the many social and emotional facets of my daughter’s illness and subsequent DDs. Using the parent transformation model (Scorgie, Wilgosh, & Sobsey, 2004) and relational dialectics theory (RDT) (Baxter & Montgomery, 1996) as sensitizing concepts, I explored my experiences through a parent-perspective lens (King et al., 1999). Ultimately, I wanted to connect with others whose lives have been touched by childhood DDs, and to play a part in the greater collaboration of sensemaking.
Keywords: Autoethnography; developmental disability; health communication; qualitative research; relational dialectics theory; transformation process model